Patient Safety Walkaround: a communication tool for the reallocation of health service resources: An Italian experience of safety healthcare implementation. Issue 41 (October 2016) - Ferorelli, Davide; Zotti, Fiorenza; Tafuri, Silvio; Pezzolla, Angela; Dell'Erba, Alessandro
Abstract : Abstract: The study aims to evaluate the use of Patient Safety Walkaround (SWR) execution model in an Italian Hospital, through the adoption of parametric indices, survey tools, and process indicators. In the 1st meeting an interview was conducted to verify the knowledge of concepts of clinical risk management (process indicators). One month after, the questions provided by Frankel (survey tool) were administered. Each month after, an SWR has been carried trying to assist the healthcare professionals and collecting suggestions and solutions. Results have been classified according to Vincent model and analyzed to define an action plan. The amount of risk was quantified by the risk priority index (RPI). An organizational deficit concerns the management of the operating theatre. A state of intolerance was noticed of queuing patients for outpatient visits. The lack of scheduling of the operating rooms is often the cause of sudden displacements. A consequence is the conflict between patients and caregivers. Other causes of the increase of waiting times are the presence in the ward of a single trolley for medications and the presence of a single room for admission and preadmission of patients. Patients victims of allergic reactions have attributed such reactions to the presence of other patients in the process of acceptance and collection of medical history. All health professionals have reported the problem of n high number of relatives of the patients in the wards. Our study indicated the consistency of SWR as instrument to improve the quality of the care.